Mannan-hydrolyzing enzymes of yeasts and yeast-like organism - Augustín, J; Zemek, J; Kuniak, L; Kocková-Kratochvílová, A (Folia microbiologica, 1980)
The ability to degrade mannan in the yeast Saccharomyces cerevisiae, i.e. the ability to produce an enzyme of the alpha-mannosidase type was tested in 57 representatives of various genera and species of yeasts and yeast-like organisms. Their growth was simultaneously monitored on soluble mannan and on 4-nitrophenyl-alpha-D-mannopyradnoside. The majority of strains produced alpha-mannosidase (EC 3.2.1.24).
Keywords: Saccharomyces cerevisiae; kvasinky; Yeasts; Mannosidases; Mannans; Polysaccharides; polysacharidy; mannany; mannosidasy